'The space between': Role-play as a tool in the treatment of child sexual abuse. Issue 3 (December 2019) - Iordanou, Christiana
Child sexual abuse is a traumatic experience which may have a negative impact on a child's attachment processes and sense of safety. A dramatherapy model that has been proposed for the treatment of child sexual abuse is the regenerative model. The regenerative model utilises role-play as a form of treatment and allows children to experiment with different roles in order to gain control of their experience and feel safe again. This article discusses a dramatherapy approach to the treatment of child sexual abuse on the basis of the regenerative model. It first introduces the model, and more specifically the concept of 'the space between' the therapist and the child. It then describes a case example and the use of role-play as a vehicle to explore emotions and thoughts and to process the traumatic experience symbolically. It concludes with the contention that dramatherapy, grounded on the regenerative model, may provide a safe space to work through the trauma relevant to child sexual abuse, in order to help a child heal and be able to form new, healthy attachment relationships.